Influence of cryopreservation and mechanical stimulation on equine Autologous Conditioned Plasma (ACP®) - Mageed, M.; Ionita, C.; Kissich, C.; Brehm, W.; Winter, K.; Ionita, J.-C. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2015)
Objective: To determine the influence of cryopreservation at two different temperatures on platelet concentration, growth factor (GF) levels and platelet activation parameters in equine ACP®; moreover, to determine if adding mechanical ACP® stimulation to freeze-thaw activation amplifies GF release from platelets. Material and methods: Firstly, blood from five horses was used to prepare ACP®. Platelet, platelet derived growth factor BB (PDGF-BB) and transforming growth factor β1 (TGF-β1) concentrations as well as mean platelet volume (MPV) and mean platelet component (MPC) were determined in fresh and corresponding ACP® samples after 2 months cryopreservation at –20 °C and –80 °C, respectively. Secondly, ACP® was prepared from blood of nine horses. Half of ACP® was activated using one freeze-thaw-cycle at –20 °C, whereas the rest was first vortexed. Their PDGF-BB and TGF-β1 concentrations were subsequently determined. Results: Platelet concentration significantly decreased after –80 °C cryopreservation. PDGF-BB level augmented significantly after both storage methods, whereas TGF-β1 concentration was not significantly altered. MPV significantly increased after –20 °C cryopreservation. Both storage regimens induced a significant MPC decrease. No significant differences in GF concentrations between the vortexed and nonvortexed samples were detected. Discussion: Both cryopreservation methods induced platelet activation, but storage at –80 °C apparently harmed the platelets without generating higher GF release than –20 °C. The mechanical stimulation process could not enhance GF release in subsequently frozen-thawed ACP®. Conclusion and clinical relevance: Storage of ACP® at –20 °C could be useful in equine practice, but, before this procedure can be recommended, further qualitative tests are needed. The mechanical stimulation technique should be adjusted in order to increase platelet activation.
Keywords: Platelet concentrate; cryopreservation; activation; horse